2005
DOI: 10.1111/j.1600-079x.2005.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against ischemia/reperfusion injury in skeletal muscle

Abstract: Melatonin has been shown to diminish ischemia-reperfusion (I/R) injury in many tissues. The main aim of this study was to evaluate the protective antioxidant effect of melatonin in skeletal muscle during I/R injury. Wistar albino rats were randomly divided into three groups. Hindlimb ischemia was achieved by clamping the common femoral artery in two groups but not in control group. Limbs were rendered ischemic for 1.5 hr; at the end of the reperfusion period of 1.5 hr muscle tissue samples were taken for the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 37 publications
1
52
0
1
Order By: Relevance
“…In addition, Quercetin has protected the neurons and effectively inhibited xanthine oxidase activity against oxidative injury in primary cultures rat cortical cells 83 . Whereas, as can be seen in a number of IR studies, it has been demonstrated that tissue MDA levels increased in skeletal muscle IR injury 84 . This effect has suppressed with the supplementation of free radical scavengers.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, Quercetin has protected the neurons and effectively inhibited xanthine oxidase activity against oxidative injury in primary cultures rat cortical cells 83 . Whereas, as can be seen in a number of IR studies, it has been demonstrated that tissue MDA levels increased in skeletal muscle IR injury 84 . This effect has suppressed with the supplementation of free radical scavengers.…”
Section: Resultsmentioning
confidence: 93%
“…Many studies have suggested the beneficial effects of nutrients or other agents such as vitamin E [45], vitamin C [46], green tea extract [45], melatonin [47,48], carbenoxolone [49], and green propolis [50,51] in reducing or preventing cerebral or muscle injury during ischemiareperfusion.…”
Section: Resultsmentioning
confidence: 99%
“…38 The effects of melatonin on ischemia---reperfusion injury in an ex vivo rat heart model was studied by Lagneux et al 39 The authors explained that the melatonin significantly reduced infarct size and the incidence of reperfusion arrhythmias. 39 In an experimental study Erkanlı et al 40 reported that melatonin has a protective effect against skeletal muscle ischemia---reperfusion injury and can reduce the incidence of compartment syndrome after chronic or acute peripheral arterial occlusions. Other studies have shown that melatonin protects kidney, 41 liver, 42 testis 43 and intestine 44 against ischemia---reperfusion injury.…”
Section: Discussionmentioning
confidence: 98%